Corporate security management : challenges, risks, and strategies - Cabric, Marko (Oxford : Butterworth-Heinemann, 2015)
Corporate Security Management provides practical advice on efficiently and effectively protecting an organization's processes, tangible and intangible assets, and people. The book merges business and security perspectives to help transform this often conflicted relationship into a successful and sustainable partnership. It combines security doctrine, business priorities, and best practices to uniquely answer the Who, What, Where, Why, When and How of corporate security. Corporate Security Management explores the diverse structures of security organizations in different industries. It shows the crucial corporate security competencies needed and demonstrates how they blend with the competencies of the entire organization. This book shows how to identify, understand, evaluate and anticipate the specific risks that threaten enterprises and how to design successful protection strategies against them. It guides readers in developing a systematic approach to assessing, analyzing, planning, quantifying, administrating, and measuring the security function.
Includes index.
Vendor-supplied metadata.
Elsevier
Keywords: Corporations -- Security measures -- Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Electronic books